Design and Development of a 3dB Quadrature Patch Hybrid Coupler - Sekharbabu, B; Narsimha Reddy, K; Sreenu, S (International Journal of Engineering and Technology, 2018)
In this paper a -3 dB, 90-degreephase shift RF quadrature patch hybrid coupler is designed to operate at 2.4GHz. Hybrid coupler is a four-port device, that’s accustomed split a signaling with a resultant 90degrees’ section shift between output signals whereas maintaining high isolation between the output ports. The RF quadrature patch hybrid coupler is used in various radio frequency applications including mixers, power combiners, dividers, modulators and amplifiers. The desired hybrid coupler is designed using FR-4 substrate with 1.6mm height in High Frequency Structure Simulation (HFSS) and the same is fabricated and tested. The designed Hybrid coupler is examined in terms of parameters like insertion Loss, coupling factor and return Loss. The simulation and measurement results are compared. Major advantages of the RF quadrature patch hybrid couplers are that they are compatible with integrated circuit technology.